2015
DOI: 10.1002/ajim.22516
|View full text |Cite
|
Sign up to set email alerts
|

Styrene‐associated health outcomes at a windblade manufacturing plant

Abstract: Background Health risks of using styrene to manufacture windblades for the green energy sector are unknown. Methods Using data collected from 355 (73%) current windblade workers and regression analysis, we investigated associations between health outcomes and styrene exposure estimates derived from urinary styrene metabolites. Results The median current styrene exposure was 53.6 mg/g creatinine (interquartile range: 19.5–94.4). Color blindness in men and women (standardized morbidity ratios 2.3 and 16.6, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…The increased occurrence of visual contrast sensitivity in the study population was also found among professionals working with styrene in reinforced plastic plants (46,47), but not among workers from a boat building plant (48). Even though styrene exposure concentrations in the investigated facility were mainly below thresholds recommended by the NIOSH or the American Conference of Governmental Industrial Hygienists, health effects occurred (28). The occurrence of such serious respiratory and visual complaints due to styrene exposure in wind blade facilities stresses the crucial need for advanced worker protection (eg, respiratory protection, eye protection) (28).…”
Section: Chemical Exposuresmentioning
confidence: 60%
See 4 more Smart Citations
“…The increased occurrence of visual contrast sensitivity in the study population was also found among professionals working with styrene in reinforced plastic plants (46,47), but not among workers from a boat building plant (48). Even though styrene exposure concentrations in the investigated facility were mainly below thresholds recommended by the NIOSH or the American Conference of Governmental Industrial Hygienists, health effects occurred (28). The occurrence of such serious respiratory and visual complaints due to styrene exposure in wind blade facilities stresses the crucial need for advanced worker protection (eg, respiratory protection, eye protection) (28).…”
Section: Chemical Exposuresmentioning
confidence: 60%
“…Sample sizes in studies that directly examined study subjects ranged from 10-603. Response rates were high in those cross-sectional studies that reported appropriate values (73-100%) (23,25,(28)(29)(30)(31)39). Proportions of female workers varied between 0-45.1%.…”
Section: Study Characteristicsmentioning
confidence: 90%
See 3 more Smart Citations